Identifikasi Problem Tingkat Kelengkapan Perangkat Instrumen Butir Soal Ujian Akhir Sekolah di MA Miftahul Ulum Kedungpanji Magetan - ema darawati istiqomah; Fifi Aida Nur Rohmah; Eni Marlina; Erna Robiyatul Adawiyah; Dzakira Keisa Alunaka Sampurna (https://ejournal.insuriponorogo.ac.id/, 2024)
Education is one of the essential sectors for a country. A nation is considered advanced when it pays significant attention to the education of its people. The human resources of a country depend heavily on its educational system. This study aims to identify issues related to the completeness of school final examination question instruments at MA Miftahul Ulum Kedungpanji, Magetan, to support efforts in improving education quality. The research employs a descriptive qualitative approach using observation and interviews to collect data on question instruments, including question blueprints, question cards, review cards, item analysis, answer keys, and scoring systems. The findings reveal deficiencies in the completeness of these instruments, which could affect the accuracy of assessing students' abilities. These findings contribute to improving question instruments to ensure more effective and accurate learning evaluations.